POSYANDU LANSIA : AKSES DAN PEMANFAATANNYA OLEH LANJUT USIA DI WILAYAH KERJA PUSKESMAS UBUD I, GIANYAR, BALI - Komang Srititin Agustina; Dyah Pradnyaparamita Duarsa; Desak Putu Yuli Kurniati (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2020)
Elderly integrated service post (Posyandu) is a place for health services which is emphasize more on promotion and preventive efforts for the elderly. In the work area of , the Community Health center (Puskesmas) Ubud I, has a sufficiently high number, but the utilization of integrated service post (Posyandu) is still low. As a result, this research aims to find out the perception of the utilization of Elderly Posyandu. Qualitative descriptive methods are used to explore and obtain in-depth information about perceptions that make it possible to get things implied about the actuality of action in utilizing the Elderly Posyandu. A total of 11 elderly women, 4 elderly men , and 1 health worker in the program was informed in this study. Information was collected with in-depth interview methods. Data were collected in May-July 2019. Data were analyzed thematically and presented using a narrative approach. This study found that the implementation of Elderly Posyandu followed the scheduling of the elderly group gymnastic. Therefore, those who visit the Posyandu were only those who participate the gymnastic group only, because those who are not in the group get less information about the implementation of integrated service post. Elderly who visit the Posyandu get health benefits (the body members have more functioning, insecure supplies, blood circulation smoothly, and sleep sleeps more soundly), healing, and a place to socialize. Perceptions of factors that encourage adherents to utilize integrated service post posyandu are the involved in the activities of Elderly Posyandu as the gymnastic instructor and the group commitee,general health check up, family support in the form of buying gymnastic equipment, and advice from the family to come to Elderly Posyandu, and suggestions by health officials to attend so the integrated health post keep exist. Elderly people who declared posyand useless because they were not present . Their Absenteeism due to the lack of information of the implementation of elderly integrated post,too busy in the household, cultural activities and work, as well as being present outside elderly gymnasitic group.